PERSAINGAN PASAR SEMPURNA PERSPEKTIF EKOMONI ISLAM - Supandi, Ach. Faqih; Umbara, Bastomi Dani; Fawaid, Achmad (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
A competitive and fair market is one of the important principles in Islamic economics. Perfect market competition, which includes transparency of information, absence of monopoly, and freedom to enter or leave the market, is highly regarded in the Islamic economic framework. From an Islamic economic perspective, perfect market competition promotes economic efficiency and social welfare. Information transparency and fairness in economic exchanges are important cornerstones in achieving this goal. Islam emphasises the importance of fairness and honesty in every aspect of life, including in economic activities. Healthy and fair market competition provides equal opportunities for all economic actors to participate and contribute to achieving the common good. The freedom to enter or leave the market also provides the possibility for innovation and sustainable economic growth. This research aims to provide a better understanding of perfect market competition from an Islamic economic perspective. Keywords: market, economy, islam